Two years of the pandemic: Impact of COVID-19 on tuberculosis management in Nigeria - Amarachi Ruth Anigbo, Lokesh Gambhir (Journal of Applied Pharmaceutical Science, 2022)
Tuberculosis case recognition and plotting is a key strategy employed by the National Tuberculosis and Leprosy Control Program in Nigeria to curtail the increasing gap of tuberculosis cases. Nigeria recorded its first case of COVID-19 in late January 2020, and since then Nigeria has currently recorded 255,753 confirmed cases with 3,143 deaths. It has currently recorded 2,699 new cases, as of 2 May 2022, among tuberculosis patients. Since the emergence of coronavirus, there has been a progressive decrease in clinic attendance and tuberculosis identification, detection, mapping, and management. The COVID-19 pandemic has impacted negatively on tuberculosis patients’ services in Nigeria as well as the nutritional status of tuberculosis patients. The present review summarizes the impact of COVID19 on the tuberculosis epidemic in Nigeria. The tuberculosis program could maximize potential resources employed to combat the pandemic, such as digital health technology and funds, and work toward strengthening the patient-centered approach of care to limit the challenges that COVID-19 presents to tuberculosis control.
Keywords: Tuberculosis, COVID-19, nutrition, Nigeria, epidemiology